AFLATOXIN OF NUTMEG IN INDONESIA AND ITS CONTROL / Aflatoksin pada Pala di Indonesia dan Pengendaliannya - Supriadi Supriadi (Puslitbang Perkebunan, 2017)
Indonesia produces the largest amount of nutmeg in the world, accounted for 66-77% of the world market. Most nutmeg plantations (99.3%) are cultivated by small holders, mainly in five provinces, i.e. North Moluccas, Moluccas, Aceh, North Sulawesi, and West Papua. Ironically, during the last 17 years (2000-2016), exported nutmeg are detected to be contaminated with aflatoxins, especially those entering the European Market, as the result 53 out 80 (62%) cases of imported nutmegs were rejected. Aflatoxin contaminating nutmeg is found in every level of market chains in the country, from the farmers, collectors and exporters, representing that aflatoxin in nutmeg is common and serious. Aflatoxins are produced mainly by two species of fungi, i.e. Aspergillus flavus and A. parasiticus. Five groups of aflatoxins are known, i.e. aflatoxin B1, B2, G1, G2, and M1, but the international legislations are concerned on the maximum limit of aflatoxin B1 and total aflatoxin (B1+B2+G1+G2) that should not exceed of 5 and 10 µg/kg, respectively. Aflatoxin in agriculture products including nutmeg can be detected by various methods, mainly by a thin layer chromatography (TLC), high performance thin layer chromatography (HPLC), andenzyme-linked immonosorbent assay (ELISA). Minimizing aflatoxin in the nutmeg should be properly managed at every level of the production processes from harvesting, drying, and packaging. Drying is the most critical one; nutmeg should be dried as soon as being harvested to keep its water content below 10%, then it be kept in a very dry condition (10oC and air humidity< 65%). ABSTRAK Indonesia merupakan penghasil pala terbesar di dunia yang memasok sekitar 66-77% pasar dunia. Sebagian besar perkebunan pala (99,2%) dibudidayakan oleh petani kecil, terutama di lima provinsi, yaitu Maluku Utara, Maluku, Aceh, Sulawesi Utara, dan Papua Barat. Ironisnya, selama 17 tahun terakhir (2000-2016), ekspor pala, terutama ke pasar Eropa, terdeteksi mengandung aflatoksin sehingga 53 dari 80 (62%) kasus pala dari Indonesia ditolak. Biji pala yang tercemar aflatoksin ditemukan pada setiap tingkat rantai pasar dalam negeri, mulai dari petani, pengumpul, dan eksportir. Hal ini menunjukan bahwa aflatoksin pada pala sudah umum dan sangat serius. Aflatoksin diproduksi terutama oleh Aspergillus flavus dan A. parasiticus. Dikenal ada 5 kelompok aflatoksin, yaitu aflatoksin B1, B2, G1, G2, dan M1, tetapi peraturan perundang-undangan Inernational hanya fokus pada batas maksimum aflatoksin B1 dan jumlah aflatoksin (B1 + B2 + G1 + G2) yang masing-masing tidak boleh melebihi dari 5 dan 10 µg/kg. Aflatoksin dalam produk pertanian, termasuk biji pala, dapat dideteksi dengan berbagai metode, terutama kromatografi lapis tipis (TLC), HPLC, dan ELISA. Upaya meminimalkan aflatoksin pada biji pala harus dilakukan secara baik pada setiap tingkat proses produksi, mulai dari panen, pengeringan, dan kemasan. Pengeringan adalah proses paling penting, oleh karena itu biji pala harus dikeringkan segera setelah dipanen untuk menjaga kadar airnya di bawah 10%. Selanjutnya biji pala kering harus disimpan dalam kondisi yang sangat kering (10oC dan kelembaban udara <65%).